PENGARUH METODE TOTAL PHYSICAL RESPONSE (TPR) TEHADAP KETERAMPILAN BINA DIRI SISWA HAMBATAN INTELEKTUAL - Latifah Puti Indani; Hidayat, Luqman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Total Physical Response (TPR) method on self-help skills of students with intellectual disabilities in bathing activities. Self-help skills are essential abilities that support independence in daily life. This study employed a quantitative approach using a One Group Pretest-Posttest Design. The participants consisted of five students with intellectual disabilities at SDLB Negeri Sungai Penuh. Data were collected through performance tests, observation, and documentation. The data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The findings indicated that the mean pretest score of 44.80 increased to 49.60 in the posttest. All students showed improvement after receiving treatment through the TPR method. The Wilcoxon Signed Rank Test yielded a significance value of 0.042, which was lower than 0.05, indicating that the alternative hypothesis was accepted. Therefore, it can be concluded that the Total Physical Response method significantly influences the self-help skills of students with intellectual disabilities in bathing activities. The TPR method can be used as an effective learning alternative because it combines verbal instructions with physical activities, enabling students to understand and perform self-help tasks more independently.